Caputo fractional model for the predator–prey relation with sickness in prey and refuge to susceptible prey - Shivani Sharma; Ravi Shanker Dubey; Arun Chaudhary (International Journal of Mathematics for Industry)
This research develops a model describing a relation between a predator and a prey where the prey species are divided into two classes i.e., susceptible prey species and the infected prey species. Furthermore, the susceptible prey species are also provided with a refuge. After this, the research expands the formulated model into a model with Caputo fractional derivative. A detailed analysis of the solution of Caputo fractional model for the predator–prey relation with a sickness in prey and a refuge to susceptible prey is done. Numerical solutions along with the simulations are briefed for the Caputo fractional model. Lastly, the phase portrait diagrams are also given for better understanding.